Identification of Content Knowledge Required for Chinese Pre-service EFL Teachers to Teach Phonics - Min Jie, Chen; Ruey Shing, Soo; Hock Seng, Goh; Guo Jie, Yin; Raja Nor Safinas, Raja Harun; Charanjit Kaur, Swaran Sing (Sciedu Press, 2022)
Empirical studies have shown that pre-service EFL teachers were not well prepared to teach phonics because they lacked a phonics instructional guide. To develop the guide, the required knowledge should include reference to a needs assessment at the initial stage of instructional design. This study aimed to identify the required knowledge with which pre-service EFL teachers can teach phonics. A survey was issued to 146 school EFL teachers who were appointed as practicum supervisors from five full-fledged schools, a focus group discussion was held among 7 EFL group directors, and a focus group discussion was conducted among 5 teacher educators. The results revealed that 7 knowledge dimensions generalised from the literature were consolidated as required knowledge, including i) phonics-related knowledge; ii) decoding rules; iii) phonics instruction approaches; iv) sight words instruction; v) sound system knowledge; vi) phonemic awareness; and vii) rule-maintenance approach. Three new findings also emerged. First, a knowledge discrepancy was identified in understanding the National English Curriculum. Second, further investigation is needed into the Curriculum Design and Study of the Curriculum and Textbooks courses in teacher preparation program. The third is the suggestion to include curriculum design and lesson planning within the knowledge required by EFL group directors, through which enlightened educators include lesson plans in the phonics instruction approaches section in the guide. Most importantly, the identified required knowledge would provide the prerequisites for investigating pre-service EFL teachers‟ present knowledge and their desired changes needed to develop a guide that prepares them to teach phonics.